Growth Before and After Trade Liberalization - Salinas, Gonzalo; Aksoy, Ataman (World Bank, Washington, DC, 2012)
The empirical study of the impact of trade liberalization has not convinced the skeptics about the economic gains after trade reforms. Some have even argued that trade reforms have led to economic collapse and to deindustrialization. Using a sample that excludes countries that were subject to major exogenous disruptions, the authors note that post-reform economic growth was 1.2 percentage points higher than before the reforms. This is remarkable considering that pre-reform periods were characterized by highly expansionary state policies and large external borrowing, and the crisis years that preceded trade liberalization in the comparisons are eliminated. Through multivariate fixed effects estimations the authors calculate that annual per capita GDP growth rates increased by up to 2.6 percentage points after the trade reforms, compared to a counterfactual that takes into consideration the evolution of several growth determinants. Moreover, trade liberalization has been followed by an acceleration of growth in investment, exports of goods and services, and manufacturing exports, and as opposed to common belief, outward orientation did not lead to significant deindustrialization and actually seems to have increased export diversification. Growth acceleration occurred irrespective of income per capita level and was quite significant in Sub-Saharan Africa. As expected, small countries benefited most from the reforms.